RELATIONSHIP BETWEEN MINDFUL ATTENTION AWARENESS AND COGNITIVE FLEXIBILITY AMONG PRE-SERVICE TEACHERS: A REGRESSION ANALYSIS - Kaur, Birender (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The main purpose of this research paper is to explore the relationship between cognitive flexibility and mindful attention awareness among pre-service teachers. Additionally, the predictive ability of mindful attention awareness towards cognitive flexibility will also be examined. Descriptive survey approach is employed to meet the purpose of the research paper. This study is executed on purposive sample of 101 pre-service teachers pursuing Bachelor of Education from Public university of Kurukshetra. Data was collected by using Cognitive Flexibility Inventory by Denis & Vander (2010) and Mindful Attention Awareness Scale by Brown & Ryan (2003). Pearson correlation analysis and linear regression analysis were employed for the statistical treatment of the data. Correlational results indicated that mindful attention awareness is significantly and positively correlated with cognitive flexibility & its sub dimensions. In linear regression analysis, it is found that mindful attention awareness explains 30% of the cognitive flexibility among pre-service teachers. Education implications and suggestions are further discussed.